CALCULATING THE CORRELATION COEFFICIENT OF LINEAR REGRESSION FOR OIL PRODUCTION AND GAS APPLICATIONS USING TURBO PASCAL VERSION 7.0 - Slamet Sigit Pujiarto; Cut Asiana Gemawaty., SKom, MMSI Cut Asiana Gemawaty., SKom, MMSI (Jurnal Sistem Informasi, 2006)
At this writing about estimate expressed or forecast in the science of statistics. Theestimate is used to find relationships or linkages between the variables of knownvalues and variables with no or unknown value.To get an estimate or forecast value and is, used a statistical method using theanalysis of the correlation coefficient and linear regression where the order isobtained from the existing sample values.